Studying of Varying for Some Mechanical Properties of Blend of Unsaturated Polyester Resin with Chloroprene and Natural Rubber Solutions - Yasser Youssef Karafallah (Tishreen University, 2019)
Thea aim of this paper is modify of general purpose unsaturated polyester resin UPE (improve of elasticity) by adding Rubber solution, and find what are the varies some of physical and mechanical properties of results blends. For execution this aim we are blended unsaturated polyester resin UPE with either Chloroprene Rubber solution (CRL ) or Natural Rubber solution (NRL) with different weight ratios (2, 5, 7, 10 and 15) % of (CRL or NRL). Results of tests are shown clear improvement for elongation at break (for all samples) with increasing of  Rubber solution in the blend, as are shown series decreasing to some of mechanical properties (Tensile strength and Young's modulus values). Morphology study was made of fracture surfaces for samples by using scanning electron microscope SEM. it is clearly that the fracture surface will change to become dull and fibrous after blending (UPE) with (NRL or CRL ), it is obviously that there are two regions were foundand phase separation between the two polymers is greater for UPE-NR .   إن الهدف من هذا البحث هو تلدين ريزين البولي استر غير المشبع للأغراض العامة GP grade UPE resin بإجراء إضافة المادة الملدنة (محلول مطاطي)، وذلك لدراسة بعض الخواص الفيزيائية والميكانيكية للمزائج الناتجة. لتحقيق هذا الهدف تم تحضير مزيج بوليميري ثنائي بين ريزين البولي استر غير المشبع مع كل من محلول مطاط الكلوروبرين ومحلول مطاط طبيعي بنسب وزنية مختلفة (2، 5، 7، 10، 15 %). أظهرت نتائج الاختبارات تحسن واضح بالاستطالة النسبية لكافة العينات بزيادة نسبة المحلول المطاطي المضاف، كما أظهرت انخفاض متتالي بخواص الشد ( مقاومة، معامل يونغ ). تم إجراء دراسة مورفولوجية للعينات باستخدام تقنية الماسح الإلكتروني الضوئي  SEMلسطح الكسر لعينة شد من الخلطة UPE-CR وأخرى من الخلطةUPE-NR حيث ظهر التجانس الجيد  في بنية المزيج للعينة الأولى مقابل انفصال طفيف في الطور للعينةUPE-NR.